Urgensi Amandemen UU Tentang Persaingan Usaha Di Indonesia: Problem Dan Tantangan - Toha, Kurnia (Jurnal Hukum & Pembangunan, 2019)
This article discusses about how urgent for the holding of an amendment to the Act No. 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, known as Competition Law. Since the effective force in 2000, the Business Competition Act has given many benefits to the economic development of Indonesia. However, there are also a lot of criticism both from academics, practitioners and commissioners of the Business Competition Supervisory Commission. This research conducted based on normative or library research using secondary data. In addition, this research was also based on a field research through interviews and focus group discussions with stakeholders. The results of the research found that there was an urgent interest for the amendment of Law No. 5 of 1999.